MANAGEMEN KEUANGAN RUMAH SAKIT SUMBER KASIH DI MASA PANDEMI - Prita Agustina; Sri Hayu (UI Cirebon (Universitas Islam Cirebon), 2022)
This study aims to explain policies, as well as the impact during the pandemic period on the finances of the Sumber Kasih Hospital in Cirebon due to late payments by the Ministry of Health. This study is descriptive analytic, and data collection was carried out by participatory observation with qualitative methods. Because the payment of claims for Covid-19 patients from the Minister of Health tends to experience delays from the date that has been determined from the term of the term according to the mutual agreement that has been stated in the legislation that has been set due to a certain factor. Meanwhile, with this condition the hospital must develop several new handling steps in these conditions, including by rearranging services at the hospital according to the new normal conditions, which of course requires new costs outside the annual budget that has been prepared every year. Therefore, the author wants to know the financial management of Sumber Kasih Hospital during the pandemic. The formulation of the right strategy for the recovery of the hospital's financial condition by utilizing time deposit funds is a financial saver in this case.